A cross-disciplinary primer on the meaning and principles of innovation - Mars, Matthew M.; Hoskinson, Sherry; Libecap, Gary D. (Emerald, 2013)
Innovation is a central mechanism in the progression of society and often captures the imagination and enthusiasm of corporate leaders, public policy makers, and so on. However, the cultural, political and social complexities of innovation that extend beyond economic and technological contexts are often overlooked. In this volume, a novel approach to deeply understanding innovation in contexts that range from the socio-cultural to the technological is presented. The fundamental principles and constructs of innovation are identified and described according to an interdisciplinary lens that gives particular focus to a variety of historical examples of innovation. This exploration leads to the development of a learning model that serves as an alternative to mainstream innovation curricula.
Keywords: Social entrepreneurship.; Social responsibility of business.; elektronické knihy; electronic books